2018
DOI: 10.1186/s11658-018-0111-3
|View full text |Cite
|
Sign up to set email alerts
|

Editorial focus: entering into the non-coding RNA era

Abstract: Recent developments in high-throughput genotyping technologies have revealed the existence of several new classes of RNA that do not encode proteins but serve other cellular roles. To date, these non-coding RNAs (ncRNAs) have been shown to modulate both gene expression and genome remodeling, thus contributing to the control of both normal and disease-related cellular processes. The attraction of this research topic can be seen in the increasing number of submissions on ncRNAs to molecular biology journals, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 114 publications
0
35
0
Order By: Relevance
“…Finally, numerous reports have illustrated the large diversity in terms of responses and clinical outcomes to COVID-19 infections. One possible variable that has not been considered is the individual differences in patient’s miRNA profiles or polymorphisms in either MTSs or miRNA sequences ( 9 , 11 , 56 , 73 ). In that regard, a recent study has suggested that COVID-19 virulence in aged patients may be due to a lower abundance of miRNAs and this may be a contributing factor in disease severity ( 34 ).…”
Section: Comparison Of the Mirna Target Sites In Human Coronavirusesmentioning
confidence: 99%
“…Finally, numerous reports have illustrated the large diversity in terms of responses and clinical outcomes to COVID-19 infections. One possible variable that has not been considered is the individual differences in patient’s miRNA profiles or polymorphisms in either MTSs or miRNA sequences ( 9 , 11 , 56 , 73 ). In that regard, a recent study has suggested that COVID-19 virulence in aged patients may be due to a lower abundance of miRNAs and this may be a contributing factor in disease severity ( 34 ).…”
Section: Comparison Of the Mirna Target Sites In Human Coronavirusesmentioning
confidence: 99%
“…MicroRNAs (miRNAs) have become an object of intense research in biomedical sciences as they play an important role in the regulation of complex biological systems by repressing gene translation 13 . For example, miRNAs are involved in inflammatory processes and have been linked to endothelial dysfunction 46 and macrophage polarization 79 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides the expression of coding RNAs, non-coding RNAs (ncRNAs) such as small and long non-coding RNAs (sncRNAs, lncRNAs) can play an important role during viral infections [ 25 ]. ncRNAs are known as post-transcriptional regulators [ 26 ], and they can participate in virus-host interactions through a variety of mechanisms [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%